Classification of the Angular Position During Wrist Flexion-Extension Based on EMG Signals - Fajardo Perdomo, María Alexandra; Guardo Gómez, Verónica; Orjuela Cañón, Álvaro David; Ruíz Olaya, Andrés Felipe (Pontificia Universidad Javeriana, 2021)
To evaluate a group of features in a myoelectric pattern recognition algorithm to differentiate between five angular positions of the wrist during flexion-extension movements.Materials and Methods: An experimental configuration was made to capture the EMG and wrist joint angle related to flexion-extension movements. After that, a myoelectric pattern recognition algorithm based on a multilayer perceptron artificial neural network (ANN) was implemented. Three different groups were used: Time domain characteristics, autoregressive (AR) model parameters, and representation of time frequency using Wavelet transform (WT). Results and Discussion: The experimental results of 10 healthy subjects indicate that the coefficients of the AR models offer the best parameters for classification, with a differentiation rate of 78 % for the five angular positions studied. The combination of frequency and time frequency resulted in a differentiation rate that reached 82 %.

Evaluar un grupo de características en un algoritmo de reconocimiento de patrones mioeléctricos para discriminar cinco posiciones angulares de la muñeca durante los movimientos de flexoextensión. Materiales y métodos: se realizó una configuración experimental para adquirir EMG y ángulo articular de la muñeca, relacionado con los movimientos de flexión-extensión. Después de eso, se implementó un algoritmo de reconocimiento de patrones mioeléctricos basado en una red neuronal artificial de perceptrón multicapa (ANN). Se emplearon tres grupos diferentes: características de dominio de tiempo, parámetros de modelos autorregresivos (AR) y representación de frecuencia de tiempo usando la transformación Wavelet (WT). Resultados y discusión: los resultados experimentales de 10 sujetos sanos indican que los coeficientes de los modelos AR ofrecen los mejores parámetros para la clasificación, alcanzando una tasa de discriminación del 78 % en cinco posiciones angulares estudiadas. La combinación de frecuencia y frecuencia de tiempo proporcionó una tasa de discriminación que alcanzó el 82 %.
Clasificación de la posición angular en flexoextensión de la muñeca a partir de señales EMG
Keywords: Medicina física; Medicine physical; Articulaciones; Joints; Biomecánica; Biomechanics; Intencionalidad de movimiento; Movement intent; Señales de electromiografía; Electromyography signals; Pattern recognition; Reconocimiento de patrones; Machine learning techniques; Técnicas de aprendizaje automático; Redes neuronales artificiales; artificial neural networks